Arterial hypertension in young people and adolescents: diagnostics and treatment - O. A. Kislyak; E. V. Petrova; D. S. Sargaeva (Кардиоваскулярная терапия и профилактика)
The current evidence on causes, diagnostics and treatment of arterial hypertension (AH) in adolescents and young people is presented. AH features in these age groups, angiotensin receptor blocker potential in prevention of AH stabilisation, as well as early prevention of cardiovascular events are discussed. The authors present their original data on the prevalence oflabile AH, autonomous dysfunction, metabolic syndrome, abdominal obesity, and hyperleptinemia in adolescents with AH.